1.2.2 Derivatives of Exponentials and Logarithms. In this section we establish the following two formulas and use them to find derivatives of various functions involving exponentials and logarithms. Proposition 1. (1) d 1 [ ln x ] = dx x (2) d [ ex ] = ex dx Proof. Let y = ln x = f(x). Then dy f(x+h) - f(x) ln(x+h) - ln x 1 x+h 1 x h = lim = lim = lim ln = lim ln1 + dx h h h x x h x h0 h0 h0 h0 = (x/h) 1 lim ln1 + h x x h0 x Let n = . Then h dy = dx n 1 lim ln1 + 1 = 1 ln e = 1 n x x n x This proves (1). To prove (2), let y = ex. Then x = ln y. We use implicit differentiation. Take the 1 dy dy derivative of both sides with respect to x. This gives 1 = . So = y = ex which proves (2). // y dx dx Example 1. Find dy if y = esin x. dx Solution. This has the form y = f(u(x)) where f(u) = eu and u(x) = sin x. The chain rule says dy du du = f '(u(x)) . By Proposition 1 one has f '(u) = eu. So f '(u(x)) = esin x. Also = cos x. Therefore, dx dx dx dy du = f '(u(x)) = (esin x)(cos x) = (cos x)esin x. dx dx This example illustrates the following rules that are useful for calculating derivatives of functions involving exponentials and logarithms. Proposition 2. If u = u(x) is some formula involving x then (3) d 1 du ( ln[u(x)] ) = dx u(x) dx (4) d du [ eu(x) ] = eu(x) dx dx 1.2.2 - 1 Proof. Let y = ln[u(x)] = f(u(x)) where f(u) = ln u. The chain rule says dy du = f '(u(x)) . By Proposition 1 dx dx 1 dy 1 du one has f '(u) = . So = which proves (3). The proof of (4) is similar. // u dx u(x) dx dy if y = ln(sin x). dx Example 2. Find Solution. Using (3) with u(x) = sin x, we have Problem 1. Find d ( ln(sin x) ) = dx 1 d sin x = cos x = cot x. sin x dx sin x dy for each of the following. dx a. y = e7x c. y = e-(x e. y = x + ln x g. y = ln i. y = e2x(2cos 3x + 3sin 3x) 2) 3x + 2 3x - 2 x + x2 ) b. y = ln( d. y = tan(ex) f. y = sec(etan(x )) h. y = x[sin(ln x) + cos(ln x)] i. y = 2 ln x sin(et) dt 0 _ j. y = ex ln(x2 + 1) l. y = k. y = tan(ln(x+1)) 2 sin(ex ) ln(tan x) ecos x If we have to take the derivative of something like y = 2x where the base is something other than e, then it is convenient to use the following proposition. Proposition 3. If a > 0 is a constant and u = u(x) is some formula involving x then (5) d [ ax ] = (ln a) ax dx (6) d du [ au(x) ] = (ln a) au(x) dx dx Proof. Write a = eln a so that ax = (eln a)x = e(ln a) x. Then d d [ ax ] = [ e(ln a) x ] = e(ln a) x (ln a) = (ln a) ax. dx dx This proves (5). (6) follows from (5) by use of the chain rule. // 1.1 - 2 dy if y = 10x. dx Example 3. Find Solution. Using (5) one has dy = (ln 10) 10x 2.303 10x. dx dy if y = 2cos x. dx Example 4. Find Solution. Using (6) one has dy d = (ln 2) 2cos x cos x = (ln 2) 2cos x (- sin x) = - (ln 2) (sin x) 2cos x dx dx - 0.693 (sin x) 2cos x. Example 5. A population of bacteria doubles every 2 hours. At time t = 0 there are 1000 bacteria. Find a. A formula for the number N of bacteria at time t b. A formula for the rate of growth at time t. c. The number of bacteria at time t = 10 and the rate of t 0 2 4 6 8 t growth at time t = 10. Solution. At the right is a table of value of t and N. Problem 2. Find a. y = 3x dy for each of the following. dx 2 b. y = N 1000 (1000)(2) (1000)(2)(2) = 1000 22 (1000)(2)(2)(2) = 1000 23 (1000)(2)(2)(2)(2) = 1000 24 1000 2t/2 esec x + 21/x x ln x If a is a positive number the y = loga x is the inverse function of the function x = ax. In other words, y = loga x is that number such that ay = x. 1 1 Examples 4. log10 1000 = 3 since 103 = 1000. log2 = - 5 since 2-5 = . 32 32 loga x can be converted to ln x by using the following proposition. Proposition 4. If a > 0 and b > 0 then (7) loga x = ln x ln a (8) loga x = logb x logb a Proof. Let y = loga x. The ay = x. Take ln of both sides and use the fact that ln ay = y ln a. This gives y ln a = ln x. Dividing by ln a gives (7). The // From (7) we get the following formulas for taking the derivative of loga x. Proposition 5. If a > 0 is a constant and u = u(x) is some formula involving x then 1.1 - 3 (8) d 1 [ loga x ] = dx (ln a) x (9) d 1 du [ loga u(x) ] = dx (ln a) u(x) dx Proof. (8) follows simply by taking the derivative of (7). (9) follows from (8) by using the chain rule. // Example 5. Find dy if y = log10 x. dx Solution. Using (8) one has dy 1 = 2.303 10x. dx (ln 10) x 1.1 - 4